2019
DOI: 10.1038/s41598-019-50643-w
|View full text |Cite
|
Sign up to set email alerts
|

Heat wave Intensity Duration Frequency Curve: A Multivariate Approach for Hazard and Attribution Analysis

Abstract: Atmospheric warming is projected to intensify heat wave events, as quantified by multiple descriptors, including intensity, duration, and frequency. While most studies investigate one feature at a time, heat wave characteristics are often interdependent and ignoring the relationships between them can lead to substantial biases in frequency (hazard) analyses. We propose a multivariate approach to construct heat wave intensity, duration, frequency (HIDF) curves, which enables the concurrent analysis of all heat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
49
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 57 publications
1
49
0
3
Order By: Relevance
“…While the analysis so far has focused on individual heatwave metric trends, studies indicate that a multivariate approach considering all metrics in a more comprehensive manner may better represent the full impact of heatwave events (Mazdiyasni et al, 2019; Ouarda & Charron, 2018). Quantifying the likelihood of heatwave events occurring with different intensities and durations can have practical applications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the analysis so far has focused on individual heatwave metric trends, studies indicate that a multivariate approach considering all metrics in a more comprehensive manner may better represent the full impact of heatwave events (Mazdiyasni et al, 2019; Ouarda & Charron, 2018). Quantifying the likelihood of heatwave events occurring with different intensities and durations can have practical applications.…”
Section: Resultsmentioning
confidence: 99%
“…Quantifying the likelihood of heatwave events occurring with different intensities and durations can have practical applications. For example, the optimal design of electrical grids during peak demand must consider both intensity and duration of excessive heat concurrently (Mazdiyasni et al, 2019). We quantified the relationship between heatwave duration and intensity to better understand their synergy, magnitudes, and variability for different time periods.…”
Section: Resultsmentioning
confidence: 99%
“…They are at least partly associated with the rapid changes occurring at the level of the global climate (Reichstein et al ., 2013) and influence the energy, water, and carbon balance of the terrestrial biosphere (Rödenbeck et al ., 2020; Xu et al ., 2020). While it is clearly important to understand how plants respond to heatwaves, the dependence of such a response on the heatwave intensity remains poorly recognized (Mazdiyasni et al ., 2019; Xu et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These limitations have led to a wide range of conclusions regarding heat wave trends across the United States and hinder our ability to understand the dynamic mechanisms responsible for heat waves (Chen & Li, 2017; Grotjahn et al, 2016). Further, while detection and attribution studies have found a slight anthropogenic influence on the severity of heat waves, the human influence on recent U.S. heat waves has not been sufficient to exceed modes of natural variability (Dole et al, 2014; Mazdiyasni et al, 2019; Min et al, 2013; Peterson et al, 2013).…”
Section: Introductionmentioning
confidence: 99%